Impact of a Novel Anticoccidial Analogue on Systemic Staphylococcus aureus Infection in a Bioluminescent Mouse Model - Hang Thi Nguyen; Henrietta Venter; Lucy Woolford; Kelly Young; Adam McCluskey; Sanjay Garg; Stephen W. Page; Darren J. Trott; Abiodun David Ogunniyi (MDPI AG, 2022)
In this study, we investigated the potential of an analogue of robenidine (NCL179) to expand its chemical diversity for the treatment of multidrug-resistant (MDR) bacterial infections. We show that NCL179 exhibits potent bactericidal activity, returning minimum inhibitory concentration/minimum bactericidal concentrations (MICs/MBCs) of 1-2 µg/mL against methicillin-resistant Staphylococcus aureus, MICs/MBCs of 1-2 µg/mL against methicillin-resistant S. pseudintermedius and MICs/MBCs of 2-4 µg/mL against vancomycin-resistant enterococci. NCL179 showed synergistic activity against clinical isolates and reference strains of Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa in the presence of sub-inhibitory concentrations of colistin, whereas NCL179 alone had no activity. Mice given oral NCL179 at 10 mg/kg and 50 mg/kg (4 × doses, 4 h apart) showed no adverse clinical effects and no observable histological effects in any of the organs examined. In a bioluminescent S. aureus sepsis challenge model, mice that received four oral doses of NCL179 at 50 mg/kg at 4 h intervals exhibited significantly reduced bacterial loads, longer survival times and higher overall survival rates than the vehicle-only treated mice. These results support NCL179 as a valid candidate for further development to treat MDR bacterial infections as a stand-alone antibiotic or in combination with existing antibiotic classes.